(untitled) (Research, Society and Development, 2022)
The ENEM PARÁ platform was created during the Covid-19 pandemic with the objective of democratizing knowledge, allowing students from the public education system in the state of Pará to have access to preparatory content for the National High School Exam – ENEM. The objective of this work is to analyze, through the access and data of the ENEM PARÁ platform, the socioeconomic profile of its users, since through this investigation it is possible to cover the different audiences that access it, which can result in a more assertive communication in the development and sharing of new platform contents. The objectives of this research are exploratory in terms of approaching the problem and are characterized as quantitative, with the use of secondary data, as these were made available by the managers of the ENEM PARÁ platform for the development of the study, and the presentation of its results took place through descriptive statistics and cross-analysis using the SPSS software, with a focus on verifying the profile of users. The results indicated that the platform has managed to achieve its goals, but most students in the state public network still do not access the service. This work seeks to contribute to the communication and digital inclusion strategies of more students from Pará on the ENEM PARÁ platform, understanding that this is an important public service that the state government has offered to those who will take the national high school exam.